The multiverse and participatory metaphysics: a theological exploration - Boulding, Jamie (Routledge science and religion series, 2022)
"This book offers a new theological approach to the multiverse hypothesis. With a distinctive methodology, it shows that participatory metaphysics from ancient and medieval sources represents a fertile theological ground on which to grapple with contemporary ideas of the multiverse. There are three key thinkers and themes discussed in the book: Plato and cosmic multiplicity, Aquinas and cosmic diversity, and Nicholas of Cusa and cosmic infinity. Their insights are brought into interaction with a diverse range of contemporary theological, philosophical, and scientific figures to demonstrate that a participatory account of the relationship between God and creation leads to a greater continuity between theology and the multiverse proposal in modern cosmology. This is in contrast to existing work on the subject, which often assumes that the two are in conflict. By offering a fresh way to engage theologically with multiverse theory, this book will be a unique resource for any scholar of Religion and Science, Theology, Metaphysics and Cosmology"--